Blurring Boundaries: The Use of Free Indirect Discourse in Contemporary Pakistani Novels - Ajmal, Muhammad; Siddiqui, Safia; Kanwal, Atiqa (Pakistan Languages and Humanities Review, 2025)
The objective of this research is to investigate free indirect discourse (FID) in contemporary Pakistani novels written in English, analyzing how these blends the narrator with each character’s thoughts. The selected novels are Home Fire by Kamila Shamsie, The Reluctant Fundamentalist by Mohsin Hamid and Cracking India by Bapsi Sidhwa. The research is supported by using Dorrit Cohn’s (1978) elaboration of different narrative modes and Banfield’s (1982) interpretation of FID within a narratology and stylistics model. The analysis reveals how personal and political tensions are expressed with the help of FID. This narrative mode not only deepens psychological realism but also constructs an ambivalent space where personal and collective histories intersect. Through close readings and comparative analysis, the research reveals how FID contributes to the evolution of the Pakistani English novel as a site of aesthetic innovation and socio-political engagement.